Decoding HSP90AA1-driven inflammatory signaling in the uveal melanoma microenvironment: an integrated analysis at single-cell resolution - Wang, Yiya; Hu, Ziqiu; Zhou, Min; Wang, Peng (Frontiers in Immunology, 2026)
PurposeDecoding key regulators in the uveal melanoma (UVM) tumor microenvironment (TME) is crucial for understanding disease progression and developing novel immunotherapy strategies. This study aims to integrate advanced computational methods and single-cell technologies to identify and validate key molecular regulators mediating inflammatory and immune signal transduction in UVM, and to explore their potential as therapeutic targets.Patients and methodsAn integrated strategy was employed, first utilizing a network-based computational screening approach to identify core regulatory genes associated with UVM progression. Subsequently, single-cell RNA-sequencing (scRNA-seq) data were analyzed to precisely delineate the expression profile of the identified key gene, HSP90AA1, across different cell populations in the UVM microenvironment at single-cell resolution. Finally, the functional role of HSP90AA1 was rigorously validated through siRNA-mediated knockdown, in vitro functional assays, and an in vivo xenograft model.ResultsOur computational analysis identified HSP90AA1 as a central hub gene. Single-cell analysis revealed that HSP90AA1 is widely expressed across multiple cell types within the UVM tumor microenvironment, particularly in malignant cells, CD8+ T cells, and macrophages. Functional validation confirmed that knockdown of HSP90AA1 significantly suppressed UVM cell proliferation, migration, invasion, and in vivo tumor growth. Mechanistically, silencing HSP90AA1 markedly inhibited key inflammatory signaling pathways (e.g., NF-κB, STAT3), leading to a significant reduction in the expression of pro-inflammatory cytokines including TNF-α, IL-6, IL-8, and CCL2, while promoting apoptosis.ConclusionBy integrating computational biology screening and single-cell resolution analysis, this study successfully decodes HSP90AA1 as a key regulator of the UVM inflammatory and immune microenvironment. These findings, grounded in single-cell insights and confirmed by rigorous experimental validation, reveal the tumor’s intrinsic “chaperone dependency” and highlight HSP90AA1 as a highly promising therapeutic target. Targeting HSP90AA1 may offer a new strategy for modulating the UVM tumor immune microenvironment and overcoming tumor progression.